The evolution of Peruvian constitutionalism and its influence on the creation of the first Court of Justice of the Republic - Llap Unchón, Lilly (2021)
The article studies the evolution of constitutionalism in Peru from a historical perspective, linking the period from the pre-independence stage to the installation of the first Court of Justice. The historical tract dates from the first period, called constitutional prehistory of 1810, with the beginning of the Cortes of Cadiz, followed by the constitutional history up to April 30, 1824. The approach, being transversal, requires the study of the liberalism of the early nineteenth century, constitutionalism, the theory of division of powers, and the jurisdictional function, whose evolution allowed the installation of the first Court of Justice. This had as its constitutional basis article 101 of the Constitution of 1823, a text that some historians consider that it did not have any influence, which this study contradicts.